Reactive oxygen species scavenging activities in a chemiluminescence model and neuroprotection in rat pheochromocytoma cells by astaxanthin, beta-carotene, and canthaxanthin - Chi-Sen Chang; Chia-Lin Chang; Guia-Hung Lai (Kaohsiung Journal of Medical Sciences, 2013)
The objective of this study was to determine chemiluminescence (CL) antioxidant activities and neuroprotective effects of astaxanthin, beta-carotene (β-carotene), and canthaxanthin on undifferentiated rat pheochromocytoma (PC12) cells. We performed three CL antioxidant assays, and the three carotenoids showed varying degrees of antioxidant activity, with astaxanthin exhibiting the highest antioxidant activity than the other two samples. Results of a pyrogallol–luminol assay revealed β-carotene to have higher antioxidant activity than canthaxanthin, whereas cupric sulfate–Phen–Vc–hydrogen peroxide (H2O2) assay showed canthaxanthin to have higher antioxidant activity than β-carotene. Luminol–H2O2 assay showed the antioxidant activity series as canthaxanthin > β-carotene at 62.5–1000 μg/mL and β-carotene > canthaxanthin at 1000–4000 μg/mL. Astaxanthin exhibited partial neuroprotective activity against H2O2 and the strongest neuroprotective activity against amyloid beta-peptide(25–35) [(Aβ)(25–35)]-induced undifferentiated PC12 cell deaths at 0.5–5.0 μM. Canthaxanthin showed partial neuroprotective activity in Aβ(25–35)-induced undifferentiated PC12 cell deaths at 1.0–5.0 μM. Astaxanthin protected undifferentiated PC12 cells from the damaging effects of H2O2 and Aβ(25–35) by the following ways: (1) scavenging superoxide anion radicals, hydroxyl radicals, and H2O2; (2) securing cell viability; (3) suppressing the production of reactive oxygen species; and (4) eliminating calcium ion influx. Our results conclusively show that astaxanthin has the merit as a potential neuron protectant.